Identification and Characterization of Dust Source Regions Across North Africa and the Middle East Using MISR Satellite Observations. Issue 13 (5th July 2018) - Yu, Yan; Kalashnikova, Olga V.; Garay, Michael J.; Lee, Huikyo; Notaro, Michael
Abstract: Motivated by limitations in current satellite‐based dust source identification techniques, this study examines dust emissions and concentrations over North Africa and the Middle East during 2000–2016 by analyzing stereo and optical products from the Multiangle Imaging SpectroRadiometer instrument on the National Aeronautics and Space Administration polar‐orbiting Terra satellite. Based on the occurrence of fast‐moving, near‐surface dust plumes from the Multiangle Imaging SpectroRadiometer cloud motion vector product, dust sources in the study region are identified in geographical depressions, including the Bodélé Depression, which represents the leading source. The West African El Djouf desert generates substantial dust emissions, which are typically underestimated by aerosol loading‐based dust source identifications. In response to local vegetation cover anomalies, dust emissions and concentrations increased at 15% year −1 over the Middle East and decreased at 12% year −1 over the central Sahel during 2001–2013 but partly recovered toward their climatological means afterward. Plain Language Summary: Dust storm activity exerts significant influence on society and the environment in North Africa and the Middle East. However, identifying dust source regions across this region remains a challenge due to the limitations and uncertainties in the current satellite‐based techniques. Here we present a new dust source identification approach based on dust plume motion, as detected by the Multiangle Imaging SpectroRadiometer instrument aboard the polar‐orbiting Terra satellite. Using the new satellite technique, dust sources in the study region are identified in geographical depressions, including the Bodélé Depression in Chad as the leading source. The West African El Djouf desert generates substantial dust emissions, which are typically underestimated by other dust source identifications. Our joint analysis of Multiangle Imaging SpectroRadiometer plume motion and aerosol data reveals that dust emissions and concentrations increased over the Middle East and decreased over the central Sahel during 2001–2013 but partly recovered afterward. Key Points: The plume motion‐based approach overcomes limitations present in other techniques and provides an independent identification of dust sources Dust sources are mostly located in geographical depressions in North Africa and Middle East, highlighting the Bodélé Depression and the West African desert Dust emissions increased (decreased) across the Middle East (central Sahel) during 2001–2013 but recently returned to their climatological means